Review of species of the Scaphoideus albovittatus group (Hemiptera, Cicadellidae, Deltocephalinae) from China, with a checklist and distribution summary for Chinese species in the genus - Chen, Fangying; Dai, Wu; Zhang, Yalin (Zootaxa, 2015)
The thirteen known leafhopper species of the Scaphoideus albovittatus species group, characterized by the presence of a dorsal white longitudinal stripe, are recognized. Eight species, including three new species, are reported in this group from China: S. albovittatus Matsumura (China: Guangxi, Guizhou, Hainan, Hebei, Henan, Hubei, Hunan, Shaanxi, Shandong, Sichuan, Xizang, Yunnan; Japan, Korea, Russia), S. coniceus Li (China: Hainan, Yunnan), S. intermedius Matsumura (China: Taiwan), S. kumamotonis Matsumura (China: Anhui, Guangxi, Guizhou, Henan, Hubei, Hunan, Jiangxi, Shaanxi, Sichuan, Xizang, Yunnan, Zhejiang; Japan), S. maai Kitbamroong & Freytag (China: Yunnan, Hainan; Thailand), S. rostratus sp. nov. (China: Yunnan), S. sagittatus sp. nov. (China: Yunnan) and S. yuani sp. nov. (China: Guangxi). The detailed morphology of the new species is described; photographs of external habitus and male and female genitalia of the species from China are given. A checklist and a key to the species in this group are also provided, as well as a checklist with distribution summaries for all valid species in the genus from China.